Overview of Indonesians sustainable nickel mining and processing - Konewka, Tomasz; Czuba, Tomasz; Oniszczuk-Jastrząbek, Aneta I. (Gospodarka Surowcami Mineralnymi – Mineral Resources Management, 2026)
The green transition will require a substantial supply of energy critical materials, including nickel emerging a critical for that. A part of the transition is the electrification of the vehicle industry. The electric vehicle (EV) has been significantly rising on major markets worldwide. In 2023 14.2 million electric vehicles were sold and which was 35 per cent over the previous year (EV-Volumes 2023). Increasing EV sales driving up global battery demand. The battery capacity reached 750 GWh in 2023, a 40 per cent increase comparing to the last year. (International Energy Agency, 2024). To keep up with rising that demand, nickel is a critical material and its production will need to expand. Indonesia is taking part in that growth reaching around half of the global supply of nickel-containing chemistries by 2030. (Transport & Environment 2023). Since 2019 Indonesia has been accelerating its plans to position the country as a key player in global EV value chain. Indonesia holds the world’s largest nickel reserves with an estimated 55 million tons (U 2024). However, not all types of nickel can be used as a material for EV batteries. The way how the nickel is mined from laterite ores leads to increase total costs for nickel production (Mudd 2010). Therefore, Indonesia should focus on including more advanced technologies into the mining process that can reduce the environment impact. The increasing number of newly operating coal plants in Indonesia increased the emissions by 21 per cent in 2022. In addition, they are off-grid coal plants which supply energy to domestic metal industry and large infrastructure projects. The key purposes of this review paper are threefold: firstly, to investigate the increasing role of Indonesia in the global battery value chain; secondly to identify the social and environmental concerns related to adopted nickel mining technology, and thirdly, to identify the ways to maintain future Indonesian mining more sustainable.